2005
DOI: 10.1578/am.31.4.2005.403
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Use of Maku'a Beach, O'ahu, Hawai'i, by Spinner Dolphins (<I>Stenella longirostris</I>) and Potential Effects of Swimmers on Their Behavior

Abstract: Spinner dolphins (Stenella longirostris) use Maku'a Beach, a small bight along the Wa'i'ana'e coast of O'ahu, as a rest site. Behavior and use patterns of Maku'a Beach by spinner dolphins and swimmers were studied in July and August of 1995 to provide baseline data on the dolphin population and to assess potential impacts of swimmers on the dolphins' resting behavior. Dolphins were observed on 52 out of 53 days, and they entered the area between 0545 and 0845 h. Their departure time varied widely. Average scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 10 publications
3
35
1
1
Order By: Relevance
“…Neither of these previous studies made observations in Bay 1, the bay with the highest values for presence here. Overall, the values from studies on the Kona Coast are lower when compared to a study done on Oahu where researchers observed spinner dolphins on 98% of days at Makua Beach (52 of 53) (Danil et al, 2005).…”
Section: Discussioncontrasting
confidence: 66%
“…Neither of these previous studies made observations in Bay 1, the bay with the highest values for presence here. Overall, the values from studies on the Kona Coast are lower when compared to a study done on Oahu where researchers observed spinner dolphins on 98% of days at Makua Beach (52 of 53) (Danil et al, 2005).…”
Section: Discussioncontrasting
confidence: 66%
“…Several studies have also shown that cetaceans perform SABs in response to disturbance. The performance of SABs are common reactions to biopsy sampling (Weinrich et al 1992, Clapham & Mattila 1993, Brown et al 1994, Gauthier & Sears 1999, Hooker et al 2001) and approaches by vessels and swimmers (Weinrich et al 2001, Williams et al 2002a,b, Coscarella et al 2003, Danil et al 2005, Lusseau 2006a. Similarly, the findings in the present study that more SABs were performed when vessels approached whales closely and that the majority of SAB bouts were performed near the time of the POCA suggest that close approaches and/or changes in vessel behavior or distance may elicit SAB performance in southern resident killer whales.…”
Section: Discussionmentioning
confidence: 99%
“…These include: decreased use of primary habitats (Allen & Read 2000, Lusseau 2005), altered spatial distribution among individuals (Au & Perryman 1982, Bejder et al 1999, 2006, Nowacek et al 2001, Jelinski et al 2002, altered behavioral budgets (Chilvers et al 2003, Coscarella et al 2003, Lusseau 2003a, Constantine et al 2004, King & Heinen 2004, Lemon et al 2006, Williams et al 2006, Hodgson & Marsh 2007), changed swimming speed or direction (Au & Perryman 1982, Kruse 1991, Au & Green 2000, Nowacek et al 2001, Williams et al 2002a,b, Jahoda et al 2003, Lusseau 2003b, Ng & Leung 2003, Bejder et al 2006, Lemon et al 2006, Williams & Ashe 2007 and altered surface and dive durations (Janik & Thompson 1996, Au & Green 2000, Jahoda et al 2003, Lusseau 2003a, b, Ng & Leung 2003. Surface active behaviors (SABs), such as tail slaps, pectoral fin slaps, leaps and jumps, may also be displayed in response to approaching vessels (Weinrich et al 2001, Williams et al 2002a, Coscarella et al 2003, Danil et al 2005, Lusseau 2006a.…”
Section: Introductionmentioning
confidence: 99%
“…This predictable behaviour and their daytime reliance on sheltered bays that are easily accessible by people (see Figure 17.1) render them more exposed and more susceptible to human disturbance compared with other dolphin species. Recent studies suggest that the resting periods for Hawaiian spinner dolphins may be interrupted or truncated by exposure to human activity, but the biological significance of these impacts requires further investigation (Danil et al, 2005;Delfour, 2007;Courbis & Timmel, 2009). Furthermore, the population of spinner dolphins along the Kona Coast of Hawai'i Island, which is the target for large-scale cetacean-watch operations, is genetically distinct from all other spinner dolphin populations in the Hawaiian Archipelago (Andrews et al, 2010).…”
Section: General Legislative Frameworkmentioning
confidence: 99%